ANALISIS PENGARUH KEADILAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN PERBEDAAN PERSEPSI KEADILAN KOMPENSASI DAN KEPUASAN KERJA BERDASARKAN JENIS PEKERJAAN PADA KARYAWAN NISSAN BANTUL YOGYAKARTA - Yuniantara, Dedy Surya (Jurnal Bisnis : Teori dan Implementasi, 2017)
With the good and fair of compensation will spur the spirit and creativity of the work so that it can show the performance, which will ultimately increase good productivity. The compensation granted to employees is very influential on the level of job satisfaction and motivation, as well as the work results.This research is purposed to exam whether compensation fairness effect on employee job satisfaction, and whether there is difference in the perception of compensation fairness and job satisfaction based on the job type. Compensation fairness is using the distributive fairness and procedural fairness constructs (Tjahjono, 2007). This research has been conducted at Nissan Bantul Yogyakarta. A total of 58 employees in marketing and non-marketing division participates provide an answer for this research. To examine the effect of independent sample t-test, the data are analyzed using SPSS.The analysis shows that there is the effect of compensation distributive fairness on job satisfaction, the effect of procedural compensation fairness on job satisfaction, and no difference in perception between marketing and non-marketing employees.